Accuracy of additive manufacturing in stomatology - Tang, Yao; Zhang, Yunfan; Meng, Zhaoqiang; Sun, Qiannan; Peng, Liying; Zhang, Lingyun; Lu, Wenhsuan; Liang, Wei; Chen, Gui; Wei, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
With the rapid developments of three-dimensional (3D) printing technology in recent decades, precise and personalized manufacturing was achieved gradually, bringing benefit to biomedical application, especially stomatology clinical practice. So far, 3D printing has been widely applied to prosthodontics, orthodontics and maxillofacial surgery procedures, realizing accurate, efficient operation processes and promising treatment outcomes. Although the printing accuracy has improved, further exploration is still needed. Herein, we summarize the various additive manufacturing techniques and their applications in dentistry while highlighting the importance of accuracy (precision and trueness).